Endometrial Cancer and Hypermethylation: Regulation of DNA and MicroRNA by Epigenetics - Kouji Banno; Iori Kisu; Megumi Yanokura; Kenta Masuda; Yusuke Kobayashi; Arisa Ueki; Kosuke Tsuji; Wataru Yamagami; Hiroyuki Nomura; Nobuyuki Susumu; Daisuke Aoki (Biochemistry Research International)
Endometrial cancer is the seventh most common cancer in women worldwide. Therefore elucidation of the pathogenesis and development of effective treatment for endometrial cancer are important. However, several aspects of the mechanism of carcinogenesis in the endometrium remain unclear. Associations with genetic variation and mutations of cancer-related genes have been shown, but these do not provide a complete explanation. Therefore, in recent years, epigenetic mechanisms that do not involve changes in DNA sequences have been examined. Studies aimed at detection of aberrant DNA hypermethylation in cancer cells present in microscopic amounts in vivo and application of the results to cancer diagnosis have also started. Breakdown of the DNA mismatch repair mechanism is thought to play a large role in the development of endometrial cancer, with changes in the expression of the hMLH1 gene being particularly important. Silencing of genes such as APC and CHFR, Sprouty 2, RASSF1A, GPR54, CDH1, and RSK4 by DNA hypermethylation, onset of Lynch syndrome due to hereditary epimutation of hMLH1 and hMSH2 mismatch repair genes, and regulation of gene expression by microRNAs may also underlie the carcinogenic mechanisms of endometrial cancer. Further understanding of these issues may permit development of new therapies.